Twenty-five-year longevity of European hake (Merluccius merluccius) from novel use of bomb radiocarbon dating in the Mediterranean Sea - Vitale, Sergio; Andrews, Allen H.; Rizzo, Pietro; Gancitano, Salvatore; Fiorentino, Fabio (Marine and Freshwater Research, 2016)
The high variability of growth and longevity estimates for European hake (Merluccius merluccius) reflects the existence of two opposing hypotheses on growth rates that differ by a factor of 2: (1) a fast-growing hypothesis (FGH) with a maximum age near 15 years; and (2) a slow-growing hypothesis (SGH) with a maximum age near 30 years. A recently established regional radiocarbon (14C) reference led to a first-time application of bomb 14C dating in the Mediterranean Sea to three of the largest-sized and potentially oldest-catch female European hake. Because age reading of otoliths is very subjective and poorly defined, these fish were aged blind with bomb radiocarbon (14C) dating as an independent estimate of validated age. The validated ages were compared with the theoretical maximum ages from the most reliable FGH and SGH von Bertalanffy growth functions. Among the three bomb 14C ages, the most diagnostic length-at-age was an alignment with the bomb 14C rise period for two of the three fish, providing validated ages of 22 years (74.5-cm total length) and 25 years (88-cm total length). The results provide estimates of length-at-age that are in agreement with the SGH and cannot be accounted for by the FGH.
Keywords: Age validation; Carbon-14; growth; lifespan; Merlucciidae